Real-Time Encryption/Decryption Algorithm with A Fractional Chaotic System of Various Data: Image, Speech, and Text - Ataş, Muhammet Taha; Güler, Hasan (Springer, 2022)
Nowadays, a fractional-order chaotic system is commonly used in digital cryptosystem applications due to its precision to initial conditions and their unpredictability. This paper proposed an encryption-decryption of image, sound, and text data based on fractional-order Rössler chaotic system. Firstly Master–Slave synchronization of fractional-order Rössler chaotic system designed with Labview to able to realize the encryption-decryption process. Fractional order Rössler system Master–Slave equations created to able to perform synchronization and then fractional-order Rössler chaotic system based Master–Slave design used in the image, sound, and text encryption-decryption separately. Image, sound, and text encryption-decryption process successfully realized. Original encrypted and decrypted data compared with each other respectively. © 2022, The Author(s), under exclusive licence to Springer Nature India Private Limited.
Keywords: Chaos theory; Cryptography; Encryption; Frational order